2015
DOI: 10.2807/1560-7917.es2015.20.8.21042
|View full text |Cite
|
Sign up to set email alerts
|

Post-discharge surveillance (PDS) for surgical site infections: a good method is more important than a long duration

Abstract: Post-discharge surveillance (PDS) for surgical site infections (SSIs) normally lasts 30 days, or one year after implant surgery, causing delayed feedback to healthcare professionals. We investigated the effect of shortened PDS durations on SSI incidence to determine whether shorter PDS durations are justified. We also studied the impact of two national PDS methods (those mandatory since 2009 ('mandatory') and other methods acceptable before 2009 ('other')) on SSI incidence. From Dutch surveillance (PREZIES) da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 21 publications
4
42
0
6
Order By: Relevance
“…Although labour intensive, a 30-day post-discharge surveillance is recommended in order to detect almost all SSI (including complicated infections) in the post-discharge period [29]. Since complex SSI cases would require medical care in the healthcare setting it would be expedient for a standardised surveillance method to be applied under those conditions [29]. In contrast to this view, a study from Brazil reported that for 93% of the women who developed SSI, the infection became apparent in the first 15 days following CS [26].…”
Section: Discussionmentioning
confidence: 99%
“…Although labour intensive, a 30-day post-discharge surveillance is recommended in order to detect almost all SSI (including complicated infections) in the post-discharge period [29]. Since complex SSI cases would require medical care in the healthcare setting it would be expedient for a standardised surveillance method to be applied under those conditions [29]. In contrast to this view, a study from Brazil reported that for 93% of the women who developed SSI, the infection became apparent in the first 15 days following CS [26].…”
Section: Discussionmentioning
confidence: 99%
“…SSI surveillance has been difficult to standardize because most infections occur post discharge and because hospitals employ a wide array of surveillance methods, such as reliance on reporting by surgeons and other hospital staff, review of postoperative micro-biology and readmissions, and chart review of all surgical cases. [8][9][10][11] The methods used impact the rates being used for performance comparisons.…”
mentioning
confidence: 99%
“…The results of our paper clearly demonstrate that the majority of the SSIs occur within 90 days, and a shorter PDS will substantially facilitate prompt feedback of surveillance results to the healthcare professionals [2].…”
Section: To the Editormentioning
confidence: 62%